Pengaruh Harga Dan Kemasan Produk Terhadap Minat Beli Konsumen Home Industri (Studi Kasus Konsumen Home Industri Makanan Di Desa Ketanggung, Kecamatan Sudimoro, Pacitan) - Hovi, Farisa Mina; Wahono, Budi; Sholehuddin, Sulton (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to analyze and explain the Influence of Product Price and Packaging on the Buying Interest of Home Industry Consumers in Home Industry Food Industry consumers in Ketanggung Village, Sudimoro District, Pacitan Regency. The sample used in this study was 65 respondents obtained from the Malhotra formula. The data analysis method used in this study is quantitative data analysis using multiple linear regression analysis. The results of this study show that simultaneously Price and Product Packaging have an effect on the buying Interest of Home Consumers in the Food Industry in Ketanggung Village, the Price variable has a significant effect on the Buying Interest of Home Consumers in the Food Industry in Ketanggung Village, and Product Packaging has a significant effect on the Buying Interest of Home Consumers in the Food Industry in Ketanggung Village. Keywords: Price, Product Packaging, Consumer Buying Interest